Posted by **John** on Tuesday, November 6, 2007 at 9:27pm.

Square roots. Woohoo. Want to check some work I did.

1. Perform indicated operations

3sqrt[3]+2sqrt[27]-sqrt[12]

3sqrt[3]+2sqrt[3*9]-sqrt[2*6]

3sqrt[3]+3*2sqrt[3]-2sqrt[3]

3sqrt+6sqrt[3]-2sqrt[3]

= 7sqrt[3]

2.Simplify

sqrt[49x^12y^4z^8]

= 7x^6y^2z^4

3.Multply

(8sqrt[6]+3sqrt[2])(4sqrt[6]-5sqrt[2]

32sqrt[36]-40sqrt[12]+12sqrt[12]-15sqrt[4]

32*6-40sqrt[12]+12sqrt[12]-15*2

192 - 28sqrt[12] -30

162 - 28sqrt[12]

or am i missing a step?

192-40sqrt[4*3]+12sqrt[4*3]-30

162-40*4sqrt[3]+12*4sqrt[3]

162-160sqrt[3]+48sqrt[3]

162- 128sqrt[3] which I think turns into 162 -56sqrt[3]

1 last square root :

Rationalize the denominator

5/sqrt[3]+sqrt[5]=

5*sqrt[3]-sqrt[5]/ sqrt[3]sqrt5[5]*sqrt[3]-sqrt[5]=

5sqrt[3]-5sqrt[5]/sqrt[9]-sqrt[15]+sqrt[15]- sqrt[25]=

5sqrt[3]-5sqrt[5]/-16 =

5sqrt[3]-5sqrt[5]/ -2

- Algebra - sqrts -
**bobpursley**, Tuesday, November 6, 2007 at 9:37pm
first two ok

3.Multply

(8sqrt[6]+3sqrt[2])(4sqrt[6]-5sqrt[2]

32sqrt[36]-40sqrt[12]+12sqrt[12]-15sqrt[4]

32*6-40sqrt[12]+12sqrt[12]-15*2

192 - 28sqrt[12] -30

162 - 28sqrt[12] ** then
**

162-28sqrt (4*3)

162-28*2sqrt3 and then multiply the 28*2

1 last square root :

Rationalize the denominator

5/sqrt[3]+sqrt[5]=

5*sqrt[3]-sqrt[5]/ sqrt[3]sqrt5[5]*sqrt[3]-sqrt[5]=

5sqrt[3]-5sqrt[5]/sqrt[9]-sqrt[15]+sqrt[15]- sqrt[25]=

5sqrt[3]-5sqrt[5]/-16 = ** No. the demoniator is (3-5)=-2
**

I have no idea where you got this line in your work, it does not make sense

5sqrt[3]-5sqrt[5]/ -2

## Answer this Question

## Related Questions

- Algebra - Square roots. Woohoo. Want to check some work I did. 1. Perform ...
- Math - simplify: 3sqrt(2)+5sqrt(4)+8sqrt(2)-2sqrt(6)
- calc check: curve length - Find the length of the curve y=(1/(x^2)) from ( 1, 1...
- Pre Cal. - Find three geometric means betwee -sqrt(2) and -4sqrt(2). A: 2, -...
- Pre Cal. - 1. Use half-angle identity to find the exact value of cos165. MY ...
- Pre-Cal - Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x...
- Pre-Cal - Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x...
- Pre-Cal(Urgent) - Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + ...
- Advanced Math - Can someone check these for me? Please? Use half-angle identity ...
- Math(Please check) - Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3...

More Related Questions